Anthropomorphic and factual approaches in Komodo dragon conservation awareness program for elementary school students: Initial study. Issue 3 (2nd July 2020) - Kamil, Puspita Insan; Susianto, Harry; Purwandana, Deni; Ariefiandy, Achmad
Abstract: Increasing wildlife awareness is a commonly used approach in community conservations programs. However, in Indonesia, this approach has rarely been quantitatively evaluated for its effectiveness. In North Flores, we carried out a short Komodo dragon ( Varanus komodoensis ) conservation awareness program for elementary school students. The program used a mixed communication approach combining an anthropomorphic storybook and factual information about Komodo behavior delivered through a presentation and a video. The results from this initial study showed that the program had improved students' knowledge of Komodo dragon biology and conservation efforts.